Bleomycin-induced skin toxicity: is it always flagellate erythema?. (29th September 2016) - Verma, Shailendra Prasad; Subbiah, Arunkumar; Kolar Vishwanath, Vinod; Dutta, Tarun Kumar
Abstract : Bleomycin-induced skin toxicity is a rare and unique complication. We report a 35-year-old man with nodular lymphocytic predominant Hodgkin's lymphoma, stage IVB, who was started on adriamycin, bleomycin, vinblastin and dacarbazine (ABVD) chemotherapy. He developed pruritic hyperpigmented, patchy skin lesions on the neck, back, chest and thighs after IA cycle of ABVD chemotherapy. Lesions were not typical flagellate rash but hyperpigmented, patchy and mildly pruritic lesions over the trunk and proximal extremities. Lesions increased with continuation of bleomycin and improved gradually after removing the drug from chemotherapy schedule. The patient was in complete remission after VI cycles of chemotherapy (AVD Regimen) and skin lesions healed with minimal residual hyperpigmentation.